O Papel da Transferência na Aprendizagem de Línguas Estrangeiras no 1º Ciclo do Ensino Básico - Gorete Ribeiro (Escola Superior de Educação de Paula Frassinetti, 2009)
For some years it has been given increasing importance to the transfer process in teaching and learning of foreign languages. This has been seen as a valuable learning strategy, which should be fostered by learners. In the case of students at an early age, this strategy assumes a more predominant role, since for most students this is the first contact with a language different from theirs. This contact with a new language questions the knowledge of learners, previously considered unique and absolute; in this way, pupils make systematically contrastive analysis, and subsequently use the transfer process.